2002
DOI: 10.1002/jmri.10041
|View full text |Cite
|
Sign up to set email alerts
|

MR‐guided bone biopsy: Preliminary report of a new guiding method

Abstract: Purpose:To evaluate the feasibility of a new MR compatible optical tracking guided bone biopsy system. Materials and Methods:Wireless optical tracker elements were connected to a bone biopsy set. Biopsies of five different anatomic areas and lesions varying from 9 mm to 40 mm (mean 25 mm) in size, were performed. Results:We were able to perform the biopsies in all cases, and the samples allowed for a pathologic diagnosis. The procedure time was limited to less than 40 minutes, and no complications occurred. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Image-guided biopsy has become an important tool to ascertain the diagnosis of malignancies in musculoskeletal [1][2][3][4] or hepatic lesions [5][6][7]. Especially in cases where computed tomography (CT) or ultrasound (US) guided methods has been unsuccessful, MR (magnetic resonance)-guided biopsy is a promising alternative, due to a high soft-tissue contrast, the option to adjust the imaging plane to the needle trajectory [8] and a good visualisation of vessels without the use of contrast agents [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Image-guided biopsy has become an important tool to ascertain the diagnosis of malignancies in musculoskeletal [1][2][3][4] or hepatic lesions [5][6][7]. Especially in cases where computed tomography (CT) or ultrasound (US) guided methods has been unsuccessful, MR (magnetic resonance)-guided biopsy is a promising alternative, due to a high soft-tissue contrast, the option to adjust the imaging plane to the needle trajectory [8] and a good visualisation of vessels without the use of contrast agents [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These results do not, however, represent the true sensitivity and specificity of low-field MRI and larger patient materials with smaller lesions are needed. In reproducing the findings obtained at high-field, low-field open MRI has potential in image-guided breast procedures [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The open configuration is also of benefit when considering image-guided procedures [19]. However, the lower signal-to-noise ratio, longer imaging times and the unavailability of fat suppression based on chemical shift may have decreased the interest in low-field MRI of the breast.…”
Section: Introductionmentioning
confidence: 98%
“…9 Ojala et al, using a method similar to ours, reported the usefulness of an optical tracking system in MR-guided bone biopsy. 10 The advantages of optical tracking are real-time operation and ease of use. Since a dedicatedˆxed implement connects the cryoprobe and pointer tool, the physician can hold the probe and pointer tool together in one hand.…”
Section: Discussionmentioning
confidence: 99%